ORGANOLEPTIC QUALITY OF BROILER MEAT FIXED WITH AZOLLA EXTRACT IN DRINKING WATER - I P.A.E., Pradita; Sriyani, N.L.P.; Siti, N.W. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the organoleptic quality of broiler meat fed Azolla extract in drinking water at different treatments carried out at Banjar Metra Kelod, Yangapi Village, Tembuku District, Bangli Regency. The design used was a completely randomized design (CRD) with 4 treatments and 4 replications which were assessed by 15 semi-trained panelists and statistically analyzed by Kruskal Wallis and Mann-Whitney . The four treatments were: (P0) Broilers who were given water without Azolla extract through drinking water. (P1) Broilers fed with 2% Azolla extract via drinking water. (P2) Broilers fed with 4% Azolla extract via drinking water. (P3) Broilers fed Azolla extract 6% via drinking water. The variables observed were organoleptic tests which included color, aroma, texture, tenderness, taste and overall acceptability. The results showed that administration of Azolla extract at a level of 4-6% through drinking water significantly (P<0.05) increased organoleptic quality but not significantly (P>0.05) on the texture variable. From the results of this study it can be concluded that the administration of Azolla extract in drinking water with a treatment of 4-6% can improve the quality of color, aroma, tenderness, taste and overall acceptability. But it doesn't really affect the texture of the meat. Giving Azolla extract to drinking water that is optimal for producing good organoleptic quality of broiler meat is a concentration of 6% seen from the panelist's acceptance of the variables of color, aroma, texture, tenderness, taste, and overall acceptance.